Pension Policies in the OECD Countries : Background and Trends. (IMF Working Papers; Working Paper ;, 1988)
Concerns about restructuring old-age income provisions and reforming public pension schemes are an OECD-wide phenomenon. This paper highlights first the background of the reform debate. Despite the divergences in the structure of public pension schemes, the main pressures for reform are strikingly similar across the OECD area and thus can be discussed under three broad headings: budgetary, economic, and social. The reform trends are presented in the second part of the paper and highlight the central features of the current reform process: reform, not revolution, extension of basic provisions; strengthening social adequacy and individual equity; and redistributing the sources of old-age income.